EVALUASI SALURAN TERSIER D.I CINGKARIANG BANDA PATAH NAGARI PADANG LUA KECAMATAN BANUHAMPU KABUPATEN AGAM - Rahmad Aliyusman; Surya Eka Priana; Yorizal Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Irrigation is the provision, regulation and distribution of water from available water sources to agricultural areas for crop needs. Irrigation is very important in the fulfillment and improvement of national food, such as the irrigation channel D.I Cingkariang Banda Patah Nagari Padang Lua. The tertiary channel of the Banda Patah Nagari Padang Lua irrigation network irrigates a rice field area of ± 100 ha. The water needs for Banda Patah's agricultural land cannot be met properly. In the Irrigation Network Planning, design analysis must be carried out which includes analysis of rainfall, calculation of discharge, and channel dimensions. The main objective of the evaluation of the Banda Patah tertiary channel is to determine the need and adequacy of water in the Banda Patah agricultural area. By upgrading the network, water needs can be provided adequately according to needs. In planning the channel dimensions obtained through the rainfall process using the Haspers method and the Gumbel method. The results of calculations from the tertiary channel dimensions in the field obtained a discharge of 1.03 m³/s and the results of the planned dimensions obtained a discharge of 5.42 m^3/s. Based on the evaluation, the dimensions of the tertiary channel of the existing Banda Patah irrigation network cannot accommodate the maximum discharge, and the dimensions of the planned channel can accommodate water at the maximum discharge.Keywords : Discharge, channel dimensions, rainfall, gumbel, haspers, tertiary channel